The relationship between fall and loneliness among older people in China: the mediating role of personality trait - Yuan, Luo; Yibo, Wu; Yuqian, Deng; Haiye, Ran; Jiaxin, Liu; Liping, Zhao (Frontiers in Psychiatry, 2023)
Aims We aimed to explore the role of personality traits between fall and loneliness. Methods A questionnaire survey was used to investigate falls, the big five personality traits, and loneliness among older people (≥ 60 years old) in China mainland. Results A total of 4,289 older people participated in the survey. There are significant differences in age, marital status, education level, residence, solitariness, and fall in relation to loneliness among older people. Falls, especially when they occurred one time increase the loneliness of older people. Agreeableness, conscientiousness, and neuroticism were significant mediating effects between falls and loneliness. Conclusion This study implied that agreeableness, conscientiousness, and neuroticism were meditating factors between falls and loneliness. In the future, we should consider the big five personality traits more to understand loneliness and offer older people interventions for reducing their loneliness. The study design was cross-sectional, so the temporal precedence of mediators and causality could not be tested. Because the data were collected retrospectively, current loneliness is likely to have confounding effects on retrospective recall.